Virologic Response Following a Switch to Dolutegravir-based Regimen in People Living with HIV/AIDS at a Tertiary Care Center in Nepal - Tamrakar, R.; Tamrakar, D. (Kathmandu University Medical Journal, 2022)
Background The dolutegravir-based antiretroviral regimen is the preferred first-line regimen for the management of people living with human immunodeficiency virus in Nepal recently. It is considered safe to transition to a dolutegravir-based regimen for children and adults on Nevirapine and Efavirenz-based regimens.Objective To determine the virologic response following the transition to a Dolutegravir-based regimen in people living with human immunodeficiency virus previously taking Nevirapine and Efavirenz-based regimen.Method This is a retrospective cohort study including people living with human immunodeficiency virus/ acquired immunodeficiency syndrome (HIV/AIDS) who were transitioned to Tenofovir/Lamivudine/Dolutegravir previously on other antiretroviral therapy regimens for at least 6 months and who had their viral load test done before transition. The medical records of patients were reviewed from records available at the antiretroviral therapy clinic of Dhulikhel Hospital. The viral load done at least 3 months after switching to the Dolutegravir-based regimen was recorded. Descriptive analysis of socio-demographic and clinical characteristics data was done.Result Fifty-seven people living with human immunodeficiency virus/ acquired immunodeficiency syndrome who transitioned to a Dolutegravir-based regimen previously on other antiretroviral therapy regimens for at least 6 months were included in this study. Tenofovir/Lamivudine/Efavirenz (47.4%), Zidovudine/ Lamivudine/Nevirapine (22.8%) and Zidovudine/Lamivudine/Efavirenz (17.5%) were the most common antiretroviral regimens before transition. The majority of the patients (86%) had suppressed viral load of fewer than 40 copies/mL before the switch. Following the transition, 96.5% of the patients had suppressed viral load of fewer than 40 copies/mL.Conclusion Dolutegravir-based antiretroviral regimen led to untransmittable viral load following a switch from Nevirapine and Efavirenz-based regimen.